RESPONSE OF VANAME SHRIMP (Penaeus vannamei) POND WATER QUALITY TO THE TRANSITION FROM BLIND FEEDING TO POST-BLIND FEEDING UP TO DOC 60 - Tri Yusufi Mardiana; Linayati Linayati; Heri Ariadi; Supito Supito; Muhammad Zulham Yahya; Abdul Halim; Imam Saefudin Fajar; Mohammad Yogi Saputra Budianto; Maullidin Ikhsan Khoerul Ikhsan; Muhammad Dicky Syamsuddin (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2026)
Vaname shrimp (Penaeus vannamei) aquaculture is highly influenced by water quality dynamics during the rearing cycle, particularly during the transition phase from blind feeding to post-blind feeding. The study aimed to describe the response of water quality in vaname shrimp ponds to changes in feeding management from the blind feeding phase through the post-blind feeding phase until DOC 60. The study was conducted at the intensive pond of CV. Mytra Pratama, Batang Regency, over one rearing cycle. Observations were made during two rearing phases: the blind-feeding phase (DOC 1–30) and the post-blind-feeding phase (DOC 31–60). The water quality parameters observed included total organic matter (TOM), ammonia (NH₃), ammonium (NH₄⁺), total ammonia nitrogen (TAN), nitrite (NO₂⁻), alkalinity, hardness, plankton abundance, total bacterial count (TBC), and total Vibrio count (TVC). Data analysis was performed descriptively based on the temporal dynamics of each parameter. The results showed that during the blind feeding phase, water quality was relatively stable, with total organic matter (TOM) ranging from 81–122 mg/L, total ammonia nitrogen (TAN) from 0.024–0.385 mg/L, and nitrite (NO₂⁻) from 0.017–0.147 mg/L. Conversely, during the post-blind feeding phase, there was a significant increase, with TOM reaching 205 mg/L, TAN reaching 2.985 mg/L, and nitrite rising sharply to 2.736 mg/L at DOC 60, accompanied by high fluctuations in aquatic biological parameters due to increased shrimp biomass and feeding intensity. The transition from the blind feeding phase to the post-blind feeding phase places greater ecological stress on the pond water system. Therefore, adaptive water-quality management is necessary to maintain environmental stability and support the sustainability of Penaeus vannamei culture at DOC 60.